2001
DOI: 10.1038/35071088
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-regulated endocannabinoids are involved in maintaining food intake

Abstract: Leptin is the primary signal through which the hypothalamus senses nutritional state and modulates food intake and energy balance. Leptin reduces food intake by upregulating anorexigenic (appetite-reducing) neuropeptides, such as alpha-melanocyte-stimulating hormone, and downregulating orexigenic (appetite-stimulating) factors, primarily neuropeptide Y. Genetic defects in anorexigenic signalling, such as mutations in the melanocortin-4 (ref. 5) or leptin receptors, cause obesity. However, alternative orexigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

49
1,120
3
29

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,453 publications
(1,201 citation statements)
references
References 29 publications
49
1,120
3
29
Order By: Relevance
“…Microinjections of the endocannabinoid 2-AG directly into the medial shell of nucleus accumbens similarly increases food intake in rats (Kirkham et al, 2002). Conversely, food-related manipulations, such as deprivation and satiety, or access to a palatable diet produce changes in CB1 receptor density and in dialysate levels of endogenous anandamide and 2-AG in nucleus accumbens and other brain areas, and modulate appetite stimulation by cannabinoids (Di Marzo et al, 2001;Harrold et al, 2002;Kirkham et al, 2002). Most relevant to this study, systemic administration of D 9 -THC in rats is reported to cause eventual increase in affective orofacial 'liking' reactions elicited by the taste of sucrose, suggesting enhancement of taste palatability (Jarrett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microinjections of the endocannabinoid 2-AG directly into the medial shell of nucleus accumbens similarly increases food intake in rats (Kirkham et al, 2002). Conversely, food-related manipulations, such as deprivation and satiety, or access to a palatable diet produce changes in CB1 receptor density and in dialysate levels of endogenous anandamide and 2-AG in nucleus accumbens and other brain areas, and modulate appetite stimulation by cannabinoids (Di Marzo et al, 2001;Harrold et al, 2002;Kirkham et al, 2002). Most relevant to this study, systemic administration of D 9 -THC in rats is reported to cause eventual increase in affective orofacial 'liking' reactions elicited by the taste of sucrose, suggesting enhancement of taste palatability (Jarrett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds, also called endocannabinoids, activate cannabinoid receptors CB1 and CB2. Activation of these receptors has been reported to induce several biological effects [4,5] such as relief of pain [6] and anxiety [7], increase of appetite [8] and reduction of intraocular pressure [9]. Additionally, the activation of CB2 receptors is involved in the dampening of inflammation, lowering of blood pressure, and suppression of peripheral pain [10].…”
Section: Introductionmentioning
confidence: 99%
“…This endogenous system has been implicated in several physiological functions including the modulation of pain (Calignano et al, 1998;Richardson et al, 1998;Walker et al, 1999), feeding (Di Marzo et al, 2001), drug dependence (Ledent et al, 1999;Lichtman et al, 2001;Gonzalez et al, 2002), excitotoxicity (Marsicano et al, 2003), anxiety (Kathuria et al, 2003), depression (Gobbi et al, 2005;Witkin et al, 2005), and cognition (Terranova et al, 1996;Marsicano et al, 2002;Varvel et al, 2005a). Of particular interest has been the discovery of fatty-acid amide hydrolase (FAAH), an integral membrane enzyme that is primarily responsible for the degradation of the endocannabinoid anandamide as well as several non-cannabinoid fatty-acid amides (FAAs; (Cravatt et al, 1996)).…”
Section: Introductionmentioning
confidence: 99%